Assessment of the Immunogenicity of Mechanically Induced Interferon Aggregates in a Transgenic Mouse Model. Issue 2 (1st December 2014) - Human, Paul; Ilsley, Helen; Roberson, Cynthia; Grovender, Eric; Van Antwerp, Bill; Fogt, Eric; Zilla, Peter
<x xml:space="preserve">Abstract</x> Pump delivery of human interferon alpha‐2B (IFNα2b) has the potential for inducing immunogenic drug aggregates. We therefore evaluated the immunogenicity of mechanically induced IFNα2b aggregates to assess this risk. Transgenic human‐IFNα2b (TG) and wild‐type (WT) FVB/N mice (n = 8 and n = 9/group, respectively) were administered mechanically agitated drug [45 Hz for 6 h (LLA) or 24 h (HLA)], chemically modified drug [low pH (pH 4.0) or metal oxidized (OXD)] or unstressed drug (native). Mice received IFNα2b (50 μg; 100 μg/mL; s.c.) formulations on days 0, 7, 14, and 21. Drug‐binding and neutralizing antibody titers were determined after 28 d. Aggregate concentrations were highest in OXD and HLA formulations but OXD had more dimers/trimers. Geometric mean titers were 1:131, 1:728, 1:1573, 1:871, and 1:10, 240 for WT mice (n = 9) and 1:207, 1:587, 1:1810, 1:571, and 1:2, 153 for TG mice (n = 8) for native, LLA, HLA, pH4, and OXD groups, respectively. Mechanical agitation of IFNα2b induced equivalent titers of immunoglobulin to that of metal oxidation, both capable of binding to or neutralizing the drug in WT and TG mice. Thus, by limiting metal contamination and by inclusion of a stabilizing agent to mitigate drug aggregation, the risk of anti‐drug immunoglobulin may be reduced in a pump delivery scenario. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:722–730, 2015